Cutting edge: MHC class I triggering by a novel cell surface ligand costimulates proliferation of activated human T cells. - Agrawal, S; Marquet, J; Freeman, G; Tawab, A; Bouteiller, P; Roth, P; Bolton, W; Ogg, G; Boumsell, L; Bensussan, A (1999)
BY55 is a human cell surface molecule whose expression is restricted to NK cells, a subset of circulating CD8+ T lymphocytes, and all intestinal intraepithelial T lymphocytes. Here, we report that BY55 is a novel NK receptor showing broad specificity for both classical and nonclassical MHC class I molecules, and that optimal binding requires a prior aggregation of MHC class I complexes. Using BY55 transfectants, we have identified functional consequences of MHC class I/ligand interactions for the class I-bearing cell. The triggering of MHC class I molecules on human T cell clones by BY55 delivered a potent proliferative signal in the presence of soluble CD3 mAb. The costimulatory signal provided by MHC class I ligation was only seen in activated, and not resting, peripheral blood T cells. This observation represents an additional and/or alternative pathway to CD28 costimulation and may be of particular relevance in memory T cells lacking CD28, such as intestinal intraepithelial T lymphocytes, which are CD28- but BY55+.